CIN coexisting with AIS is a risk factor for residual disease after conization for cervical adenocarcinoma in situ - Zeng, Rong; Guo, Yulin; Zou, Miao; Wang, Chaonan; Wu, Xufeng (Frontiers in Oncology, 2025)
IntroductionCompared to definitive hysterectomy, cervical conization with negative margin remains a controversial management for AIS currently. Our study aimed to evaluate (1) the effect of conization with negative margin alone or subsequent hysterectomy, (2) the effect of LEEP and CKC with or without subsequent hysterectomy, and (3) the correlation between clinicopathologic characteristics and residual disease after conization.MethodsThis retrospective study involved 59 AIS patients who had negative margins through conization, with or without subsequent hysterectomy, focusing on clinicopathologic characteristics and outcomes.ResultsA total of 59 patients with a median age of 34 years were followed for 3–95 months (median follow-up period: 35 months). Furthermore, 20 patients underwent subsequent hysterectomy (hysterectomy group) and 39 patients underwent conization alone (conization group). There were 24 patients who obtained negative margin through LEEP (LEEP group) and 35 patients through CKC (CKC group). Firstly, no significant difference in the rate of disease recurrence (2.6% vs. 0%, P-value = 1.0), HR-HPV positivity at first follow-up (15.4% vs. 5.0%, P-value = 0.404), or HR-HPV clearance (84.6% vs. 95.0%, P-value = 0.404) was found between the conization and hysterectomy groups. Secondly, no significant difference in the rate of disease recurrence (0% vs. 2.6%, P-value = 1.0), HR-HPV positivity at first follow-up (8.3% vs. 10.3%, P-value = 0.689), or HR-HPV clearance (91.7% vs. 89.7%, P-value = 0.689) was found between the CKC and LEEP groups. Lastly, five patients (25.0%) with residual disease were found in the hysterectomy group. All five patients were CIN coexisting with AIS (AIS-plus-CIN), and AIS-plus-CIN was identified as an independent risk for residual disease after conization (HR: 3.64, 95% CI: 1.01–4.26, P-value = 0.027). Moreover, one patient developing a recurrent disease was AIS-plus-CIN in the conization group.DiscussionEither CKC or LEEP with negative margin could achieve an equivalent effect compared with subsequent hysterectomy and could be recommended as an alternative therapy for AIS. However, subsequent hysterectomy is advised for AIS-plus-CIN.